2022
DOI: 10.1093/eep/dvac015
|View full text |Cite
|
Sign up to set email alerts
|

European epidemiological patterns of cannabis- and substance-related congenital cardiovascular anomalies: geospatiotemporal and causal inferential study

Abstract: As prenatal and community cannabis exposures have recently been linked with congenital heart disease (CHD), it was of interest to explore these associations in Europe in a causal framework and space-time context. Congenital anomaly data from Eurocat, drug-use data from the European Monitoring Centre for Drugs and Drug Addiction, and income from the World Bank. Countries with rising daily cannabis use had in general higher congenital anomaly rates over time than those without (time: status interaction: β-Est. =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Interestingly a companion paper to this one has shown that the VACTERL syndrome (Vertebral, anorectal, cardiac, tracheo-esophageal fistulae/esophageal atresia, renal and limb anomalies) [ 83 ] was strongly and causally linked with European cannabinoid exposure [ 15 , 84 ]. Since renal anomalies are part of the VACTERL syndrome this finding also imputes renal abnormalities in the overall pattern of uronephrological congenital anomalies (UCA’s).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly a companion paper to this one has shown that the VACTERL syndrome (Vertebral, anorectal, cardiac, tracheo-esophageal fistulae/esophageal atresia, renal and limb anomalies) [ 83 ] was strongly and causally linked with European cannabinoid exposure [ 15 , 84 ]. Since renal anomalies are part of the VACTERL syndrome this finding also imputes renal abnormalities in the overall pattern of uronephrological congenital anomalies (UCA’s).…”
Section: Introductionmentioning
confidence: 99%
“…UHRF1 is also a key regulator of cell growth. Growth inhibition explains some of the growth-inhibitory actions of cannabis, as described in studies involving babies' heads, brains, and hearts ( 191 , 195 , 196 , 201 , 203 , 205 , 207 , 319 321 ).…”
Section: Epigenomicsmentioning
confidence: 99%
“…There are various strengths and limitations to the present conceptualization. The strengths include the remarkable consistency across the many epidemiological studies, which clearly demonstrates the genotoxic harms of cannabis exposure in several different international jurisdictions, in relation to both the congenital anomalies [ 28 , 36 , 37 , 40 , 45 , 46 , 49 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] and cancer [ 22 , 23 , 24 , 25 , 26 , 30 , 41 , 232 ], and, indeed, now also in aging [ 53 , 54 ]. Similar results in many different studies are clearly mutually supportive and strengthen the overall quality of the body of evidence.…”
Section: Mechanisms Of Cannabinoid Genotoxicitymentioning
confidence: 99%
“…For the reader who is unfamiliar with this epidemiological literature, it should be pointed out that most of the modern epidemiological studies referred to are not just observational ecological studies of convenience which happen to show a particular association. Many of the best studies used a formal space–time analysis and the quantitative tools of causal inference to introduce a pseudo-randomized quasi-experimental paradigm from which it is entirely appropriate to invoke causal associations [ 28 , 36 , 37 , 40 , 45 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%